Altitude training: Myths and methods - Mester, J.; de Marees, M; Knuth, S.; Simon, A.; Wahl, P. (Dimensions of performance: A Symposium on altitude training in Berlin 3. September 2005, 2005)
1. Introduction 2. Hypoxic Training: Methods, protocols and markers 3. Empirical Methods: Different strategies 4. Results: Group based studies and individual results 5. Individuality: Training revisited 6. Summary